Etude Phytochimique Et Activité Antibactérienne De Deux Espèces De Lavande Autochtones Au Maroc : «Lavandula stoechas L. et Lavandula dentata L.» - Bachiri, Lamiae; Echchegadda, Ghizlane; Ibijbijen, Jamal; Nassiri, Laila (European Scientific Journal, ESJ, 2016)
In the present work, the aim is to compare the chemical composition and antibacterial activity of two lavender Species "Lavandula stoechas L." and "Lavandula dentata L.", belonging to wild flora of Morocco. Thus, a phytochemical screening was performed on the aerial part of invested plants, and no qualitative difference was detected between the studied species. Indeed, both contain catechin and gallic tannins, flavonoids (anthocyanins, flavones and catechols), sterols and triterpenes, in addition to combined anthracene compounds (C-glycosides). Whereas, the dosage of crude aqueous extracts showed that the contents of secondary metabolites, such as polyphenols, flavonoids and total and condensed tannins were higher in L. dentata. Also, the essential oils of the aerial part, obtained by hydrodistillation gave higher yields in L. dentata than L. stoechas. Finally, antibacterial activity tests were performed on four strains of bacterial pathogens (Staphylococcus aureus "Gram+," and Escherichia coli; Klebsiella pneumoniae and Proteus mirabilis which are Gram -) with both essential oils and crude aqueous extracts. The results obtained showed that essential oils have a powerful effect, particularly that of L. dentata on S. aureus, with an inhibition diameter about 30 mm. The crude extracts showed moderate antibacterial activity against Gram - and had no effect on Gram +.